PENGARUH KUALITAS PELAYANAN BERDASARKAN DIMENSI SERVQUAL TERHADAP KEPUASAN KONSUMEN PADA WAROENG SPESIAL SAMBAL CABANG MAGELANG - Tri Yulianingsih; Ivo Novitaningtyas (Jurnal Manajemen dan Bisnis, 2021)
Most restaurants are adapting to the Covid-19 pandemic conditions through improving the quality of service based on health protocols, as is Waroeng Special Sambal Magelang. This study aims to determine how the influence of service quality based on SERVQUAL (tangible, reliability, responsiveness, assurance, and empathy) on consumer satisfaction at Waroeng Special Sambal Magelang during the Covid-19 pandemic. This study uses a quantitative approach by using primary data from respondents through questionnaires. The population in this study are consumers who make purchases at Waroeng Special Sambal Magelang. The number of samples used is 100 respondents based on the purposive sampling method. The data analysis method used is multiple linear regression analysis based on SPSS. The results show that simultaneously service quality has a positive and significant effect on customer satisfaction, and the dominant variable is reliability. While partially, only tangibles and reliability variables have a significant positive effect. The results have implications for restaurant managers to consider factors in service quality that can affect customer satisfaction. Thus, it is expected that restaurants can provide quality service to make consumers satisfied and have the potential to become loyal customers.